Early detection of subclinical heart disease via nonlinear heart rate variability in a doxorubicin-induced cardiomyopathy experimental model in dogs - Hasegawa, Mizuki; Sasaki, Mayuko; Umemoto, Yui; Hayashi, Rio; Hatanaka, Akari; Hosoki, Marino; Farag, Ahmed; Hamabe, Lina; Shimada, Kazumi; Matsuura, Katsuhiro; Yoshida, Tomohiko; Takahashi, Ken; et al. (Frontiers in Veterinary Science, 2026)
BackgroundEchocardiography is the first choice for assessing the structure and function of the heart, but it is unclear for detecting subclinical changes. In recent years, abnormal heart rate variability (HRV) has received attention for its ability to identify patients at risk for developing heart failure. HRV analysis in veterinary medicine is predominantly limited to linear analysis, which primarily reflects advanced heart disease. In contrast, nonlinear HRV analysis holds the potential for early detection of heart disease, but its quantitative evaluation remains rare.ObjectivesThis study aimed to evaluate the feasibility of using HRV for the early heart disease detection in clinical settings, with a focus on doxorubicin (DXR)-induced myocardial damage in dogs.Animals and methodsSix healthy female dogs with no abnormalities on physical examination, blood pressure, electrocardiography (ECG) and echocardiography were selected in this study. The dogs had an average age of 1.2 years and an average body weight of 8.1 kg. After recording blood pressure, ECG and echocardiography, the dogs were fitted with a Holter ECG, and measurements were taken for 2 days. Following the removal of the Holter ECG, DXR at 30 mg/m2 was administered over 30 min, repeated every 3 weeks, up to a maximum cumulative dose of 180 mg/m2. Each measurement was taken before the first and after the final DXR dose.ResultsThere were no changes in recommended parameters of left ventricular systolic function (FS: 34.4% [33.9–42.8] vs. 37.8% [34.7–42.8], p = 0.73, GLS EN: −19.1% [−21.3 – −17.5] vs. −18.0% [−19.3 – −17.3], p = 0.68). However, the Poincaré plot of nonlinear HRV significantly reflected increased sympathetic activity (SD1/SD2: 0.58% [0.57–0.60] vs. 0.42% [0.40–0.45], p = 0.008, SD2/SD1: 1.8% [1.76–1.82] vs. 2.5% [2.3–2.7], p = 0.008).ConclusionThe finding that nonlinear HRV analysis reflected early increased sympathetic activity associated with DXR administration in dogs is an important step forward in enhancing the clinical application potential of HRV.